Implementasi Pancasila dalam Resolusi Konflik Global : Studi Kasus Peran Indonesia dalam Mediasi Internasional - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Abdurrahman Hadi; Livia Istiqomah; Jenny Saharany Aulia Putri; Muhammad Asro Al Munawir (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Pancasila, as the foundation of the Indonesian state, embodies universal values that are relevant for resolving global conflicts. Indonesia, as a nation that upholds these values, has played a significant role as a mediator in various international conflicts, employing a diplomatic approach based on the principles of Pancasila. This article aims to examine the application of Pancasila values in Indonesia’s diplomacy, focusing on case studies of Indonesia’s role in mediating the Palestinian conflict, the Rohingya crisis, and tensions within ASEAN. This research adopts a qualitative approach with a case study methodology, enabling a deep understanding of Indonesia’s diplomatic dynamics in the context of these global conflicts. Additionally, the research analyzes official documents, academic journals, and Indonesia’s foreign policies to provide a comprehensive picture of the effectiveness of a Pancasila-based approach. The results of the analysis indicate that despite existing geopolitical challenges and the dominance of global power structures, the Pancasila-based approach can serve as an effective model for conflict resolution, emphasizing dialogue, social justice, and humanity as the foundation for solutions. Indonesia’s diplomacy, which prioritizes Pancasila values, has proven its relevance in fostering a more just and peaceful world order, while strengthening Indonesia’s position as a moral leader in international diplomacy.